Mid- to Long-Term Survivorship Analysis of a Second-Generation Highly Cross-Linked Polyethylene in Total Hip Arthroplasty - Yeroushalmi, David; Lygrisse, Katherine A.; Sharan, Mohamad; Maher, Nolan A.; Zuckerman, Joseph D.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2020)
The emergence of highly cross-linked polyethylene (HCLPE) has drastically improved survivorship of implants used in total hip arthroplasty (THA), as demonstrated by midterm outcomes. However, there is limited data evaluating long-term outcomes and wear rates of these liners. Therefore, the aim of this study is to evaluate the longest-to-date follow-up of a specific second-generation HCLPE liner, the progression of wear rate, and its relation to acetabular cup positioning. A retrospective study was conducted on patients who underwent THA between January 2001 and December 2005 using a specific second-generation HCLPE liner. Annual liner wear rate (mm/year) was calculated in this group as well as acetabular positioning through abduction angle (degrees). Failures and reason for failures such as periprosthetic fracture, dislocation, and osteolysis were noted when applicable. Forty hips of 35 patients were included in this study with a clinical and radiographic follow-up of 13.4 ± 2.2 years (range: 10.0–16.7 years). Linear and volumetric wear rates were calculated to be 0.037 ± 0.020 mm/year and 22.94 ± 12.07 mm3/year, respectively. No radiographic femoral or acetabular osteolysis was observed in any of the cases. One patient required revision due to complications unrelated to the liner. No significant relationship could be established for acetabular component abduction angle and linear wear rate (p = 0.690, Spearman's rho = 0.03). Our study demonstrates comparable liner wear rates to that of other second-generation HCLPE liners in long-term follow-up. The XLPE liner continues to exhibit minimal progression of linear wear when compared with previous midterm studies and maintains a low rate of postoperative complications requiring revision THA surgery. Further studies are warranted to assess long-term wear and survivorship between this specific liner and comparable HCLPE models.
Keywords: HCLPE; highly cross-linked polyethylene; XLPE; survivorship; liner; total hip arthroplasty; THA; second generation